Oral Squamous Cell Carcinoma: A Case Report and Review of Literature - Boza Oreamuno DDS MSc, Yadira (Odovtos - International Journal of Dental Sciences, 2016)
Oral squamous cell carcinoma (OSCC) is the most common malignancy in the oral cavity. Its etiology is multifactorial, being the most important risk factors tobacco smoking and alcohol consumption. Predominantly affects older people, mostly male, from 40 years with a peak at the age of 60 years. The most common locations are the tongue and floor of the mouth. The clinical presentation is variable, highlights ulcerating type, such as leukoplakia, erythroplasia or a combination of both. Often their behavior is aggressive and the diagnosis is often made at a late stage, with lesions of considerable size and invasive in depth. The aim of this paper is to present a case of OSCC in advanced stage, located in the left buccal mucosa and demonstrate the importance of early diagnosis.